Können wir autonom unser Gehirn manipulieren, bis wir jemand anderes sind?: zum Verhältnis von Neuroethik, Bewusstseinsphilosophie und Theologie - Ohly, Lukas (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2014)
Neuroscience has raised great doubt regarding the idea of autonomy in human decision-making. Many people have come to use pharmaceutical and even medical treatments for enhancing their brain. This article reveals an important feature of the phenomenon of subjectivity in order to answer the ethical question regarding the point at which the subject destroys herself in voluntarily manipulating her brain. The article draws out the difference between experience and the content of an experience. Both features of subjectivity are based on a theological platform which is called the «feeling of utter dependency” (Friedrich Schleiermacher). Subjects are permitted to manipulate themselves with view to the content of their experiences. On the other hand, they destroy themselves when the touch the process of experience and play God.